Italian local goat breeds have better milk coagulation properties than cosmopolitan breed. Issue 1 (14th December 2020) - Currò, Sarah; Manuelian, Carmen L.; De Marchi, Massimo; Goi, Arianna; Claps, Salvatore; Esposito, Luigi; Neglia, Gianluca
Abstract: Native goat breeds play an important role both in the safeguarding of biodiversity and the development of local economy. This study aimed to evaluate milk coagulation properties (MCP) of local (Garganica, Girgentana, Maltese, Mediterranean Red) and cosmopolitan (Saanen) goat breeds. From May to August 2018, 46 goats were sampled monthly in an experimental farm; milk samples were analysed for fat, protein and lactose percentages, pH, SCC and MCP. Data were evaluated through a mixed linear model with repeated measures, including breed, month of lactation and parity as fixed effects. Month of lactation affected all studied traits, and breed affected MCP, protein percentage, lactose percentage and pH. Milk composition and coagulation properties were better in local breeds than Saanen. In particular, milk of local breeds was richer in protein percentage, and coagulated and reached 20 mm of curd firmness on average 3.14 and 2.56 min earlier than Saanen, respectively. Moreover, the firmest curd was observed in Girgentana (31.44 mm) and the weakest in Garganica (21.72 mm). Rennet coagulation time and curd firmness decreased towards the end of lactation, differing significantly between May (10.62 min and 31.69 mm, respectively) and August (8.33 min and 20.69 mm, respectively), whereas curd-firming time only differed between May and June–July. In conclusion, milk of local breeds showed better milk coagulation ability than the cosmopolitan breed. Highlights: Breed and month of lactation were important sources of variation of goat MCP. Local goat breeds showed better MCP than Saanen. Valorisation of the milk from the local breeds might be a tool to preserve native genetic resources.